2012
DOI: 10.1080/17470218.2012.697905
|View full text |Cite
|
Sign up to set email alerts
|

Observation of another's action but not eye gaze triggers allocentric visual perspective

Abstract: In the present paper, we investigated whether observation of bodily cues-that is, hand action and eye gaze-can modulate the onlooker's visual perspective taking. Participants were presented with scenes of an actor gazing at an object (or straight ahead) and grasping an object (or not) in a 2 × 2 factorial design and a control condition with no actor in the scene. In Experiment 1, two groups of subjects were explicitly required to judge the left/right location of the target from their own (egocentric group) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
53
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 38 publications
9
53
3
1
Order By: Relevance
“…Similar results are found when making judgements about the location of another item in relation to a person (e.g. is the flower on his left or his right) (Kessler and Thomson 2009), and the propensity to make egocentric transformations is modulated by the social cues in the image such as gaze direction (Mazzarella et al 2012). …”
Section: Egocentric Transformationssupporting
confidence: 63%
“…Similar results are found when making judgements about the location of another item in relation to a person (e.g. is the flower on his left or his right) (Kessler and Thomson 2009), and the propensity to make egocentric transformations is modulated by the social cues in the image such as gaze direction (Mazzarella et al 2012). …”
Section: Egocentric Transformationssupporting
confidence: 63%
“…However, when gaze and action convey incongruous information making the agent's intention ambiguous, gaze direction becomes relevant and may increase spontaneous perspective taking. These findings may help to reconcile inconsistent findings concerning the relative contributions of gaze and action cues to perspective taking (e.g., Tversky and Hard, 2009; Mazzarella et al, 2012) by showing that, rather than depending on specific bodily cues (and not others), perspective taking is influenced by the attribution of intentions to others.…”
Section: Discussionmentioning
confidence: 59%
“…Mazzarella et al (2012) reported that action triggered perspective-taking, but gaze cues did not. They suggests that this may be because eye gaze is not critically relevant, as grasping is, to understanding what an actor is currently doing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations